2021
DOI: 10.1021/acssuschemeng.0c08157
|View full text |Cite
|
Sign up to set email alerts
|

Eco-friendly Synthesis of Nanoporous Magnesium by Air-Free Electrolytic Dealloying with Recovery of Sacrificial Elements for Energy Conversion and Storage Applications

Abstract: The synthesis of nanoporous Mg with minimal surface oxide coverage has been hindered by its high chemical reactivity. Herein, we demonstrate the fabrication of three-dimensional bicontinuous nanoporous Mg with ligament and pore sizes in the range of 20–30 nm using air-free electrolytic dealloying with recovery of the sacrificial material. The starting material consists of a magnesium–lithium parent alloy with lithium as the sacrificial component. During selective electrolytic leaching in an anhydrous lithium-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(46 citation statements)
references
References 53 publications
0
46
0
Order By: Relevance
“…For these experiments, the pellets were broken into 4–5 bulk pieces by tapping with a spatula, and hydrolysis took place on a single compacted piece of ∼20 mg. We found that 6.01 mL of H 2 was produced per gram of NP-Al/LiBH 4 in the 5 th hour of submersion for the 80:20 wt % composition pellet and 4.72 mL of H 2 produced per gram NP-Al/LiBH 4 for the 90:10 wt % composition. Because a single piece is tested, the expected H 2 generation curve as a function of time is expected to be different from our previous experiments using nanoporous metals crushed into fine, free-flowing powders for H 2 gas generation because of the differing surface areas available between the free-flowing powder form and the compact pellet form. Thus, a low amount of H 2 is released and observed initially from these pellets; however, a longer and steady H 2 generation rate can be achieved as shown in Supporting Information Figure S1, where 4.81 mL of H 2 per gram is detected after 21 h of submersion for the NP-Al/LiBH 4 80:20 wt % pellet. The prolonged, near-steady H 2 generation is a result of the compressed pellet form factor that reduces the total surface area available for reaction with water and represents the speed at which water can penetrate deeper into the pellet.…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…For these experiments, the pellets were broken into 4–5 bulk pieces by tapping with a spatula, and hydrolysis took place on a single compacted piece of ∼20 mg. We found that 6.01 mL of H 2 was produced per gram of NP-Al/LiBH 4 in the 5 th hour of submersion for the 80:20 wt % composition pellet and 4.72 mL of H 2 produced per gram NP-Al/LiBH 4 for the 90:10 wt % composition. Because a single piece is tested, the expected H 2 generation curve as a function of time is expected to be different from our previous experiments using nanoporous metals crushed into fine, free-flowing powders for H 2 gas generation because of the differing surface areas available between the free-flowing powder form and the compact pellet form. Thus, a low amount of H 2 is released and observed initially from these pellets; however, a longer and steady H 2 generation rate can be achieved as shown in Supporting Information Figure S1, where 4.81 mL of H 2 per gram is detected after 21 h of submersion for the NP-Al/LiBH 4 80:20 wt % pellet. The prolonged, near-steady H 2 generation is a result of the compressed pellet form factor that reduces the total surface area available for reaction with water and represents the speed at which water can penetrate deeper into the pellet.…”
Section: Resultsmentioning
confidence: 77%
“…An alternative solution to high-pressure H 2 tanks is solid-state H 2 storage in lightweight materials including chemical hydrides such as magnesium hydride (MgH 2 ), aluminum hydride (AlH 3 ), lithium borohydride (LiBH 4 ), and sodium borohydride (NaBH 4 ), which can release H 2 upon heating. However, these chemical hydrides suffer from poor H 2 adsorption/release kinetics under practical temperatures and pressures, as well as a lack of practical regeneration methods. Another promising alternative to high-pressure H 2 tanks is H 2 generation by metal hydrolysis, during which a reactive metal such as Al, Mg, or Zn spontaneously reacts with water to generate H 2 , heat, and the corresponding metal hydroxide as the only solid byproduct. The typical hydrolysis reactions for Al, Mg, and Zn are given in eqs − with Δ G calculated at 298 K: …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, electrochemical dealloying processes have been modified to produce nanoporous materials from air- and water-sensitive metals, which holds great potential towards producing hydrogen on-demand by hydrolysis and energy storage applications. Fu et al synthesized 3D bicontinuous nanoporous Mg (pore sizes ~20–30 nm) from Mg-Li parent alloy using air-free electrochemical dealloying [ 71 ]. In this process, the sacrificial component of the parent alloy (Li) was recovered by using a pure Li foil as a counter electrode, thus, making the process eco-friendly.…”
Section: Dealloying For Fabricating Nanoporous Materialsmentioning
confidence: 99%